Investigating the impact of social networks on women working from home (WFH) in alleviating psychological distress - Ariffin, Adlina; Abdul Khaiyom, Jamilah Hanum; Kartiwi, Mira; Azizan, Awis Rumaisya (Malaysian Communications & Multimedia Commission, 2023)
In Malaysia, women constitute 38.9% of the total workforce. They play a fundamental role in contributing to the financial and economic strength of the country and their families. However, when the world was hit by COVID-19 that forced them to work from home, they faced many challenges in performing their different roles all at once. Within their homes they are expected to multitask – from being a wife, mother and employee – without any clear distinction in terms of time and space in performing household and professional responsibilities. This situation has led them to experience psychological distress. To address the issue, this study was conducted to investigate how social networks are employed by women working from home in alleviating psychological distress. The research was undertaken using mixed method approach, via physical survey questionnaire and virtual online semi-structured interview. It was found that women who work from home face a lot of challenges especially in juggling between different responsibilities. In addition, women in the rural areas seemed to experience a mild to extremely severe levels of depression, anxiety and stress, higher than their counterparts those in urban areas who were able to manage these psychological elements better. Based on the findings, it is recommended that a centralised support system and fair working-from-home policy should be established to help our working women achieve a good and healthy state of mind.